Child survivor of rabies in India: a case report. (1st October 2020) - John, Biju; Kumar, Shyam; Kumar, Sudeep; Dalal, S. S.; Mohimen, Aneesh
ABSTRACT: A 4-year-old boy was admitted with an acute onset fever for 4 days and drowsiness for 3 days, followed by progressive flaccid weakness of both lower limbs and encephalopathy soon after admission. He had sustained a WHO Class III stray dog bite 2 weeks previously and had received three doses of post-exposure rabies vaccination with purified vero cell vaccine but not rabies immunoglobulin. He was diagnosed with rabies based on the presence of rabies virus neutralising antibody in CSF (Day 1 1:128 and Day 26 1:2048) and typical findings on neuro-imaging. Rabies viral RNA was not detected in CSF, in saliva or on nuchal skin. The child survived with supportive treatment alone but he has extensive neurological sequelae. This report demonstrates the detailed clinico-investigative profile of a child who survived rabies following inadequate post-exposure prophylaxis and adds to the sparse knowledge of this usually fatal condition. Abbreviations: ADEM, acute disseminated encephalomyelitis; CBNAAT, cartridge-based nucleic acid amplification test; CSF, cerebrospinal fluid; EEG, electroencephalogram; GCS, Glasgow coma scale; EVM, eye opening, best verbal response, best motor response; IM, intramuscular; IVIg, intravenous immunoglobulin; MRC, Medical Research Council; MRI/FLAIR, magnetic resonance imaging/fluid attenuation inversion recovery; PCR, polymerase chain reaction; RFFIT, rapid fluorescent focus inhibition test; RIg, rabies immunoglobulin; RNA, ribonucleic acid; WBC, white blood cells; WHO, World Health Organization.